A Mersiya by Muhamed Nerkesija - Mašić, Madžida (Prilozi za orijentalnu filologiju, 2017)
This work presents in a new light a mersiya, poem written by Muhamed Nerkesija, poet from Sarajevo, upon the death of his close friend, alim and qadi Kafzade Fejzi. First part of the paper gives a general review of the development of elegic genre in the literatures of the Oriental and Islamic circle. Elegies, poems expressing the pain because of the death of a dear person, transitoriness of life, in Ottoman literary tradition have a prominent place, and in the most of the world cultures elegies are the primary literary genre. In diwan literature this genre is called mersiya. It is poetry composed with a goal to express the sorrow felt after somebody’s death, and in order to point out the virtues of the deceased, and for a poet to indicate his relationship to the deceased. In the body part of the paper, we have focused on characteristics of form and content of this mersiya which are in general the main characteristics of the poems of this genre. In the last part we present the mentioned mersiya and give its integral translation.